Sungai Sehat, Masa Depan Sejahtera: Aksi Bersama Memperingati Hari Air Sedunia Melalui Pembersihan Air Sungai di Negeri Latu, Kabupaten Seram Bagian Barat - Handy E P Leimena; Behlul Tupamahu; Riska Fun; Hesty Patty; Ashar Patty; Nurul L Pattimura; Asmi Gamar Ely; Rahma S. Wakano; Sukran Pellu; Yusril Fun; Rivan Ukratallo; Naila Patty; Tri Wahyuningsih Susanto (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Rivers serve as an essential source of water for fulfilling community needs. Many residents continue to rely on nearby rivers to obtain clean water for daily activities. However, public awareness regarding river cleanliness remains limited. The low level of community concern for the preservation of riverine environments has contributed to water pollution and the degradation of overall water quality. This community service program was carried out with the objective of improving the environmental quality of the river in Negeri Latu, West Seram Regency, through a river-cleaning initiative. Engaging 15 members of the PELELATU Community, the activity was conducted on 22 March 2022, coinciding with the celebration of World Water Day. The stages of implementation included an initial site survey to identify critical pollution points, the removal of vegetation obstructing river flow, and the collection of waste accumulated along the riverbanks. This program successfully achieved its primary goals, namely enhancing the ecological condition of the river while simultaneously strengthening the community’s collective awareness of the importance of conserving natural resources for the sustainability of life in Negeri Latu.